2001
DOI: 10.1002/path.904
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and activation of eosinophils in inflammatory bowel disease using an improved immunohistochemical technique

Abstract: Eosinophils are a recognized feature of inflammatory bowel disease (IBD), but their tissue distribution and functional importance in Crohn's disease (CD) and ulcerative colitis (UC) remain obscure. This study describes an improved immunohistochemical protocol to identify eosinophils in full thickness bowel wall specimens of IBD (n=40) and their in situ relationships with the chemoattractants eotaxin and RANTES. Eosinophils were identified using immunohistochemistry with a combination of monoclonal antibodies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 30 publications
(46 reference statements)
5
57
0
Order By: Relevance
“…During inflammatory responses, IL-13 has been shown to regulate an array of eosinophil-sensitive functions including eotaxin production and eosinophil recruitment and survival (33)(34)(35)(36). Elevated levels of eotaxin have also been observed in serum and biopsy samples from patients with UC consistent with a role for eotaxin in eosinophil accumulation into the GI tract during UC (6,11,37,38). Using eotaxin Ϫ/Ϫ mice, we demonstrate an important role for eotaxin in the recruitment of eosinophils into the colon during experimental UC.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…During inflammatory responses, IL-13 has been shown to regulate an array of eosinophil-sensitive functions including eotaxin production and eosinophil recruitment and survival (33)(34)(35)(36). Elevated levels of eotaxin have also been observed in serum and biopsy samples from patients with UC consistent with a role for eotaxin in eosinophil accumulation into the GI tract during UC (6,11,37,38). Using eotaxin Ϫ/Ϫ mice, we demonstrate an important role for eotaxin in the recruitment of eosinophils into the colon during experimental UC.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, there has been increasing interest in the involvement of eosinophils in the pathogenesis of UC (6). Elevated levels of eosinophils have been observed in colonic biopsy samples from UC patients and increased numbers of this cell have been shown to correlate with morphological changes to the GI tract, disease severity, and gastrointestinal dysfunction (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Eosinophils have been observed in the intestinal tissues of patients with Crohn's disease and ulcerative co- litis as well as in the airways of asthmatics, but their contribution to the observed pathology of these diseases remains uncertain. 14,52 Eosinophil accumulation in the mucosa is a common feature observed during DSS-induced colitis in mice. 16,17 We and others have previously shown that TLR2 signaling in response to the commensal microflora is important in limiting mucosal injury during DSS colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils are not histological landmarks in either Crohn's disease or in ulcerative colitis, though they do represent the major portion of all granulocytic cells in active or fulminant IBD, independent of the type of disorder. Moreover, IBD patients with a significant tissue eosinophilia demonstrate increased expression of eotaxin and RANTES (95). It has also been demonstrated that flare-ups are correlated with an elevated faecal excretion of eosinophil cationic protein (96).…”
Section: Eosinophilia Associated With ôNoneosinophilicõ Inflammationsmentioning
confidence: 99%
“…Interestingly, a quantitative assessment of the eosinophils in the mucosa of patients with ulcerative colitis showed that patients having a benign course of the disease and a good response to treatment have significantly higher eosinophil levels in the mucosa than do those patients who have an aggressive form of the disease and fail to respond to medical treatment (97). All these observations suggest that the eosinophils and their mediators are actively involved in the inflammatory process of both Crohn's disease and ulcerative colitis Their role is certainly more than that of an Ôinnocent bystanderÕ (95). However, Crohn's disease bears many features of a T H1 type inflammation, whereas ulcerative colitis is closer aligned with allergies (98).…”
Section: Eosinophilia Associated With ôNoneosinophilicõ Inflammationsmentioning
confidence: 99%